Nexus among militarization, economic development, FDI, stock market development and renewable energy usage and CO₂ emissions - Muhammad Husnain; Waris Ali (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
CO2 significantly contributes to greenhouse gas (GHG) emissions. This investigation determines the impact of militarization, economic growth (EG), FDI, renewable energy usage on CO2 emissions in three highly militarized countries of Asia: Pakistan, India, and China (PIC). This research used strata software and employed an ARDL approach to test the hypothesized relationships by using data from sampled countries for the years ranging from 1993 to 2017. The results revealed that military expenditures, EG, and FDI positively impact CO2 emissions, whereas renewable energy sources reduce CO2. The results provide some useful insights for regulators and policymakers to control environmental pollution in PIC countries. Further, this research sets guidelines for future research.
Keywords: 330; CO2 emissions; economic growth; stock market development; foreign direct investment (FDI); military expenditure